Training and Mentoring: Developmental-based assessment procedures for young children will be provided - Erna Budiarti; Nata Priatna; Susi Mulyawati; Suhartinah Suhartinah; Aisyah Aisyah; Ayu Dwi Widia (Jurnal Dedikasi, 2023)
Evaluating and appraising are crucial in comprehending and facilitating young children's progress in early childhood education. Ensuring that the assessment methods are practical and suitable for this age group is essential. The objective of this study is to apply and assess a development-oriented evaluation method in early childhood education to enhance the quality of educational services provided to children. The community service approach is implemented through the collaborative efforts of educational institutions, communities, and parents. The evaluation methodology encompasses multiple facets of child development, surrounding religion and character, language, physical motor skills, cognitive abilities, social-emotional aptitude, and artistic talents. The community service method provides educators and parents with training sessions on development-based assessment techniques. Furthermore, support is offered for implementing this evaluation technique in official and informal educational settings. The evaluation results indicate a rise in comprehension regarding early childhood development among educators, parents, and the community. Implementing this evaluation focused on development, yielding substantial advantages in early identification of children's capabilities and requirements. In addition, this strategy fosters enhanced collaboration between educators and parents in facilitating the comprehensive development of children. The aim is for the findings of this study to serve as a foundation for creating educational policies that are both inclusive and adaptable to the requirements of early childhood in society.